KARAKTERISTIK POMPA SENTRIFUGAL DENGAN SUDU IMPELLER STREAMLINE - Yurianto, Yurianto (ROTASI, 2001)
This research is used to obtain the centrifugal pump characteristic based on of impeller vane shape between normaland streamline vane. Both characteristic are found by comparing of each impeller vane, main data of both impeller vane aresuction & discharge pressure; flow rate; torsion and impeller speed.Efficiency; torsion and head of centrifugal pump with streamlined impeller vane are larger than normal impeller